The angiotensin II type 2 receptors protect renal tubule mitochondria in early stages of diabetes mellitus - Micakovic, Tamara; Papagiannarou, Stamatia; Clark, Euan; Kuzay, Yalçın; Abramovic, Katarina; Peters, Jörg; Sticht, Carsten; Volk, Nadine; Fleming, Thomas; Nawroth, Peter Paul; Hammes, Hans-Peter; Alenina, Natalia; et al. (Kidney international, 2018)
Diabetic nephropathy correlates more closely to defective mitochondria and increased oxidative stress in the kidney than to hyperglycemia. A key driving factor of diabetic nephropathy is angiotensin II acting via the G-protein-coupled cell membrane type 1 receptor. The present study aimed to investigate the role of the angiotensin II type 2 receptor (AT2R) at the early stages of diabetic nephropathy. Using receptor binding studies and immunohistochemistry we found that the mitochondria in renal tubules contain high-affinity AT2Rs. Increased renal mitochondrial AT2R density by transgenic overexpression was associated with reduced superoxide production of isolated mitochondria from non-diabetic rats. Streptozotocin-induced diabetes (28 days) caused a drop in the ATP/oxygen ratio and an increase in the superoxide production of isolated renal mitochondria from wild-type diabetic rats. This correlated with changes in the renal expression profile and increased tubular epithelial cell proliferation. AT2R overexpression in tubular epithelial cells inhibited all diabetes-induced renal changes including a drop in mitochondrial bioenergetics efficiency, a rise in mitochondrial superoxide production, metabolic reprogramming, and increased proliferation. Thus, AT2Rs translocate to mitochondria and can contribute to reno-protective effects at early stages of diabetes. Hence, targeted AT2R overexpression in renal cells may open new avenues to develop novel types of drugs preventing diabetic nephropathy.
Gesehen am 14.04.2020